A dialogic analysis of Hello Barbie's conversations with children. Issue 1 (April 2020) - Steeves, Valerie
This paper analyses Hello Barbie as a commercial artefact to explore how big data practices are reshaping the enterprise of marketing. The doll uses voice recognition software to 'listen' to the child and 'talk back' by algorithmically selecting a response from 8000 predetermined lines of dialogue. As such, it is a useful example of how marketers use customer relationship management systems that rely on sophisticated data collection and analysis techniques to create a relationship between companies and customers in which both parties are positioned as active participants who are able to obtain what they wish from the interaction. I use dialogic analysis to see how Mattel 'makes sense' of the dialogue as a dialogic partner. I argue that, in spite of the rhetoric of instantaneity and personalization, in which the technology is positioned as an immediate response to a child's imagination, Mattel's dialogic communication is both asynchronous and carefully crafted to fit the child's responses within predetermined consumer subjectivities that are crafted to encourage particular kinds of consumption. Although the dialogue spoken by Hello Barbie is able to situate Barbie as an active subject, the control exercised by the company in order to elicit data for customer relationship management purposes and steer the dialogue to brand-friendly messages relegates the child to a passive role. Accordingly, the doll fails to deliver the promises of customer relationship management.